Kontekstualisasi Tafsir As Sya'rowi dalam Kehidupan Modern - Karlopi, Putri Guspida; Pathurrahman (STIQ al-Lathifiyyah Palembang, 2024)
Abstract This study aims to examine the development of Tafsir As-Syarawi in modern life, explore how this tafsir remains relevant and accepted by various Muslim circles, and identify the contribution of Sheikh As-Syarawi in answering various challenges and contemporary issues through his work. This study uses a qualitative method with a library research approach to analyze various sources and interpretations used by Sheikh As-Syarawi in interpreting the Qur'an, as well as how his linguistic, contextual, and scientific approaches can be applied in modern life. The results of this research This study shows that Tafsir As-Syarawi by Sheikh Muhammad Mutawalli As-Shaarawi remains relevant in modern life. First, this tafsir uses clear and simple language, making it easier to understand for various groups, including the younger generation and those who do not have a deep Islamic scientific background. Second, As-Syarawi relates the verses of the Quran to relevant social, cultural, and moral contexts in daily life, providing a practical view for Muslims in facing the challenges of modern times. This tafsir also emphasizes the moral and ethical values of the Quran, helping to shape the character and behavior of Muslims according to religious teachings. As-Syarawi offers concrete solutions to contemporary issues such as education, economics, and social relations. His open approach to modern science allows this interpretation to remain relevant in an ever-evolving scientific and technological context. Through media such as lectures on television and digital platforms, Sheikh As-Syaravi's teachings can reach millions of people around the world, including the younger generation. The life and example of Sheikh As-Syarawi as a moderate and integrity scholar inspires Muslims to practice the teachings of Islam wisely and with compassion.